Indications and complications of percutaneous endoscopic gastrostomy in a quaternary care center in Nepal - Chaurasia, Shivaom; Shrestha, Umid Kumar; Pokheral, Babu Ram (Journal of Advances in Internal Medicine, 2025)
BACKGROUND AND AIMS Percutaneous endoscopic gastrostomy is essential for long-term enteral nutrition, particularly in patients with neurological or structural swallowing impairments. Despite global use, there has been no data from Nepal. This study evaluates indications, endoscopic findings, and complications of gastrostomy tube insertion in a quaternary care center in Nepal. METHODS This retrospective study analyzed patients who underwent new gastrostomy tube placement at Nepal Mediciti Hospital from April 2018 to April 2025. Data on demographics, clinical indications, endoscopic findings, and complications within one month related to the procedure, were collected and analyzed using descriptive statistics. RESULTS The most common indication for percutaneous endoscopic gastrostomy placement was cerebrovascular accident (36.7%), followed by Parkinson disease (16.7%) and traumatic brain injury (16.7%). The mean age of patient was 58.7 years (SD ±20.49) among which majority of patients (23.2%) were between 60–69 years age group. Endoscopic findings were normal in 89.3% of cases. Reported complications were minimal, with 82.1% of patients experiencing no complications. Minor gastric bleeding (8.9%), tube dislodgement (3.6%), wound infection (3.6%), and tube leakage (1.8%) were the complications observed. CONCLUTION The PEG tube insertion is safe and effective, with minimal early complications. Its crucial role in managing neurological and oncological disorders by optimizing the proper nutrition emphasizes the need for careful patient selection. Further research with more sample size and long term follow up is needed to substantiate its safety and long-term outcomes, especially in resource-limited settings in Nepal.